Exploring effects of dietary coffee pericarp addition on growth, meat quality, gut flora in white-feather broilers - Linxian Shan; Jun He; Ruijuan Yang; Jinya Dong; Zezhu Du; Shengjie Duan; Yanmei Li; Xiuli Lu; Yan Shen; Jianyang Fu; Shengmei Gao; Xiaocui Du; et al. (Poultry Science)
The incorporation of coffee pericarp into poultry diets enhances chicken meat quality by modulating intestinal flora. This study investigates the effects of coffee pericarp on chicken meat quality through an analysis of growth performance, physical parameters, chemical composition, volatile compounds, and gut microbiome. The results demonstrate that adding coffee pericarp to the diet reduces drip loss and pH while improving meat color and increasing the levels of crude protein, amino acids, unsaturated fatty acids, and volatile compounds. Furthermore, coffee pericarp influences the metabolism of these compounds by increasing the relative abundance of beneficial bacteria, such as Firmicutes and Bacteroidetes, thereby enhancing meat quality. In conclusion, incorporating 2.5 % fermented coffee pericarp effectively regulates beneficial bacteria and significantly boosts the volatile compound content in white feather broilers, which is crucial for improving meat flavor and the economic viability of poultry production.